Pengaruh Kepemimpinan Spiritual Terhadap Budaya Organisasi Sebagai Variabel Mediasi Di Umkm Pamekasan (Laboratorium Sosiologi FISIP Universitas Jember, 2023)
Changes in the competitive environment require an organizational adaptation process to succeed its vision and mission. Organizations will experience obstacles to develop when they do not pay attention to social changes in their environment. This study uses (SEM-PLS) to analyze data quantitatively on the influence of spiritual leadership and organizational culture on organizational performance variables through an innovative act as a mediating variable. The sampling method used was purposive sampling with a total of 40 respondents from Micro, Small and Medium Enterprises (MSMEs) in Pamekasan Regency. By using the theory of organizational culture, spiritual leadership and innovative acts this study found that first, spiritual leadership has a positive effect on organizational performance. Second, organizational culture has a positive effect on performance; and Spiritual leadership influences organizational culture which is mediated by innovative acts. The people of Pamekasan district tend to have a hard working character especially in business. However, changes in their economic business will always intersect with the spirituality in their economic innovation behavior because spiritual values have become part of the daily life of the Madurese people. Keywords: Spiritual Leadership, Organizational Culture, Innovation Behavior, (Micro, Small and Medium Enterprises), Madurese Society